Influence of hormones and medium components on expression of dipyranocoumarins in cell suspension cultures of calophyllum inophyllum L. - Pawar, Kiran D.; Thengane, Shubhada Ratnakar (Process Biochemistry, 2009)
Cell suspension cultures were initiated separately from leaf and nodal/internodal calluses for the study of influence of hormones and medium components on biomass growth and expression of dipyranocoumarins. Highest 6.2 times biomass was enhanced in suspension cultures of nodal/internodal callus supplemented with threefold total sulphate. Picloram 8.28 mu M along with BAP 8.88 mu M enhanced 295.05 times inophyllum A in suspension cultures of leaf callus whereas IBA 14.70 mu M along with BAP 4.44 mu M in suspension cultures of leaf callus enhanced 1065 times inophyllum B. IBA 4.90 mu M alone in suspension cultures of nodal/internodal callus enhanced maximum 616 times inophyllum C. Only IBA 9.80 mu M in suspension cultures of leaf callus enhanced 23.22 times inophyllum P. Variation in nitrate and sulphate had maximum positive influence on expression of inophyllums A and C and vitamins had maximum positive influence on expression of inophyllums A, C and B. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Calophyllum inophyllum; dipyranocoumarins; Expression pattern; HPLC; Medium components; Suspension culture

Influence of abiotic elicitation on production of dipyranocoumarins in suspension cultures of calophyllum inophyllum L. - Pawar, Kiran D.; Thengane, Shubhada Ratnakar (Acta Physiologiae Plantarum, 2011)
Effects of elicitation with heavy metals such as copper, cadmium, chromium (abiotic elicitation) and supplementation of CaCl(2) on production of dipyranocoumarins (inophyllums) in suspension cultures of leaf and stem callus of Calophyllum inophyllum were studied. The optimum timing for elicitor introduction was found to be the 10th day after initiating the suspension cultures. Cadmium as abiotic elicitor in suspension cultures of stem callus was found best to elicit maximum production of inophyllums A, C, and calophyllolide while cadmium in suspension cultures of leaf callus was found best for eliciting maximum production of inophyllums B and P. Inophyllum D was the only dipyranocoumarin whose highest production was achieved when 1.0 mM chromium was used as abiotic elicitor in suspension cultures of stem callus. Out of the three abiotic elicitors used, none could result biomass growth. Only incorporation of CaCl(2) in suspension cultures resulted biomass growth. A maximum of 35.26-fold biomass growth was achieved when suspension cultures of stem callus were incorporated with 2.0 mM CaCl(2). CaCl(2) was noted to have no positive influence on production of most of the dipyranocoumarins under study.
Keywords: Abiotic elicitation; Calophyllum inophyllum; dipyranocoumarins; Heavy metals; Suspension culture

Influence of endophytic fungal elicitation on production of inophyllum in suspension cultures of Calophyllum inophyllum L. - Pawar, Kiran D.; Yadav, Amit V.; Shouche, Yogesh S.; Thengane, Shubhada Ratnakar (Plant Cell Tissue and Organ Culture, 2011)
The influence of dried cell powder and culture filtrates of endophytic fungi on production of inophyllum in cell suspension cultures of leaf- and stem-derived callus of Calophyllum inophyllum was investigated. Two fungi, Nigrospora sphaerica and Phoma spp., endophytic to C. inophyllum, were isolated from leaf tissues, and were identified by both 18S rRNA gene amplification and sequencing. Elicitation of suspension cultures of both callus types of C. inophyllum with dried cell powder and culture filtrates of both fungi consistently elicited production of inophyllum A, B, C, and P. In comparison to stem-derived callus, suspension cultures of leaf-derived callus enhanced production of most inophyllum. Of the four inophyllum studied, the highest production of inophyllum A, C, and P was achieved in elicited suspension cultures of leaf-derived callus. Suspension cultures of stem-derived callus enhanced production only of inophyllum B. When suspension cultures of leaf-derived callus were elicited with 40 mg dried cell powder of Phoma spp., a level of 751-fold (6.84 mg/100 g elicited biomass) of inophyllum A was produced, compared to control. Whereas, a level of 414-fold (6.22 mg/100 g elicited biomass) of inophyllum B was produced when suspension cultures of stem-derived callus were elicited with 20 mg dried cell powder of N. sphaerica. When compared to control, a 10% culture filtrate of N. sphaerica in suspension cultures of leaf-derived callus elicited inophyllum C and P production by 928-fold (7.43 mg/100 g elicited biomass) and 750-fold (1.5 mg/100 g elicited biomass), respectively.
Keywords: Biotic elicitation; Calophyllum inophyllum; Endophytic fungi; Inophyllum; Suspension cultures